Topological Defect Evolutions Guided by Varying the Initial Azimuthal Orientation - Yanchun Shen; Jinbing Wu; Jingge Wang; Saibo Wu; Wei Hu (Applied Sciences)
Topological defects are a key concern in numerous branches of physics. It is meaningful to exploit the topological defect evolutions during the phase transitions of condensed matter. Here, via varying the initial azimuthal orientation of the square alignment lattice in a hybrid cell, the topological defect evolution of liquid crystal during the nematic (N)–smectic A (SmA) phase transition is investigated. The director fields surrounding ±1 point defects are manipulated by predesigning the initial azimuthal orientation. When further cooled to the SmA phase, spiral toric focal conic domain (TFCD) arrays are formed as a result of twisted deformation suppression and unique symmetry breaking after the phase transition. The variation in the azimuthal orientation causes the TFCDs to degenerate from infinite rotational symmetry to quadruple rotational symmetry, thus releasing new textures for the SmA phase. Landau–de Gennes numerical modeling is adopted to reproduce the director distributions in the N phase and reveal the evolution of the topological defects. This work enriches the knowledge on the self-organization of soft matter, enhances the capability for the manipulations of topological defects, and may inspire new intriguing applications.